Evaluating Maqāṣid al-Sharīʿah Compliance in DSN–MUI Fatwas Governing Islamic Fintech and Crypto Instruments - Farrel Izham Prayitno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid expansion of digital Islamic financial products, including fintech services and crypto-related instruments, has intensified regulatory reliance on fatwas while simultaneously raising concerns about their substantive alignment with the objectives of maqāṣid al-sharīʿah. Existing studies largely focus on legal permissibility and operational feasibility, leaving limited systematic evaluation of whether regulatory fatwas meaningfully realize ethical and governance-oriented Sharia objectives. This study aims to assess the extent of maqāṣid al-sharīʿah compliance of DSN–MUI fatwas governing digital Islamic financial products. Employing a normative–analytical design integrated with a maqāṣid-based simulation model, the study analyzes secondary and publicly available data, including selected DSN–MUI fatwas and supporting regulatory documents, and operationalizes maqāṣid principles into structured evaluative indicators. The simulation results indicate that the analyzed fatwas achieved moderate overall maqāṣid compliance, with relatively strong performance in wealth protection and permissibility dimensions, but weaker alignment in justice, harm prevention, and broader public interest objectives. Scenario-based analysis further shows that enhanced governance-oriented interpretation yielded only marginal improvements, suggesting structural rather than interpretative limitations in existing regulatory frameworks. These findings contribute theoretically by positioning maqāṣid al-sharīʿah as an evaluative governance framework rather than a purely justificatory doctrine and practically by offering a replicable model for assessing substantive Sharia compliance in digital finance regulation. The study underscores the importance of integrating explicit maqāṣid benchmarks into fatwa formulation to ensure that digital Islamic finance advances ethically, sustainably, and in line with the broader objectives of Islamic law.